Enantioselective Intermolecular Heck and Reductive Heck Reactions of Aryl Triflates, Mesylates, and Tosylates Catalyzed by Nickel. (9th December 2020) - Huang, Xiaolei; Teng, Shenghan; Chi, Yonggui Robin; Xu, Wenqiang; Pu, Maoping; Wu, Yun‐Dong; Zhou, Jianrong Steve
Abstract: Nickel‐catalyzed intermolecular Heck reaction of cycloalkenes proceeds well with aryl triflates, mesylates and tosylates in excellent enantiomeric ratios. The asymmetric reductive Heck reaction also works with a 2‐cyclopentenone ketal, which is equivalent to conjugate arylation of the enone itself. Abstract : Nickel catalysts efficiently promote enantioselective Heck reaction of aryl triflates, mesylates and tosylates in excellent ee values. Asymmetric reductive Heck reaction with a ketal of 2‐cyclopentenone also proceeds well, which is equivalent to conjugate arylation of the enone itself.